System for Magnetic Monitoring of High Voltage Motors MM6212 - Kartalovic, Nenad M; Babić, Blagoje; Ilić, Nikola; Milosavljević, Srđan (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper suggests the possibility of diagnosing different types of failure in working induction motors using a device for spectral analysis of axial leakage flux, which has been developed by the Electrotechnical Institute Nikola Tesla. A search coil, which can be of different diameters, was mounted concentrically on the shaft at the rear of the motor. The electromotive force (emf) on each of the coils, created as a result of weak magnetic field changes, has a low amplitude. Following the necessary amplifications and adjustments, the signal is digitised on acquisition. In the fast Fourier transform (FFT) stage, the sampled and quantised digital time-based signal is converted to a frequency spectrum. Changes in spectral content are used to identify developing faults.
Keywords: Spectral analysis; high voltage motor; magnetic monitoring